How can I prove this identity?

(1 + sinØ + cosØ):(1 - sinØ + cosØ) =
(1 + sinØ) : cosØ

1 answer

Work on the left hand side:
(1 + sinØ + cosØ)/(1 - sinØ + cosØ)
multiply both the numerator and denominator by (1-sinφ+cosφ) and simplify:
((1+cosφ)^2-sin&hi;^2)/(1-sinφ+cosφ)^2
=2cosφ(1+cosφ)/[2(1-sinφ)(1+cosφ)]
=2cosφ/[2(1-sinφ)]
=cosφ/(1-sinφ)
Now multiply top and bottom by (1+sinφ)
cosφ(1+sinφ)/(1-sin²φ)
=cosφ(1+sinφ)/cos²φ
=(1+sinφ)/cosφ
Similar Questions
  1. how do you solve this problem?1+sinØ/cosØ +cosØ/1+sinØ = 2secØ and cosß- cosß/1-tanß = sinßcosß/sinß-cosß
    1. answers icon 2 answers
    1. answers icon 1 answer
  2. As the answer to:(tanØ * cosØ/ sinØ) + cotØ * sinØ * tanØ* cscØ I got 2, is that correct?
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions